Peripheral giant cells granuloma: a clinical case report - Vergara-Hernández, Clara Inés; Díaz-Caballero, Antonio; Arévalo-Tóvar, Luisa (Revista Facultad de Odontología Universidad de Antioquia, 2010)
The peripheral giant cell granuloma (PGCG) is a pseudotumoral exophytic lesion, very rare in oral cavity, it is primarily located in the premolar and molar area of the mandible, it usually presents bleeding and rapid growth, also, is associated with aggression or irritating factors (extraction, trauma, plaque, tartar, faulty restorations, chronic infection, food impaction, among others). Its treatment consists of surgical excision, removing the irritating factors. Within its differential diagnosis are the hyperparathyroidism brown tumor, cherubism and aneurysmal bone cyst, which have the same histological pattern as the peripheral giant cell granuloma. This is a description of a clinical case of a female patient, age 52 who attended the College of Dentistry of the University of Cartagena because she presented a tumor located in the vestibular and lingual gingival area of anterior and lower zone associated with abundant bacterial plaque and subgingival calculus. The surgeon made the surgical excision of the lesion, extraction of teeth affected by the marked bone loss, and curettage. The sample was sent to the pathology lab which confirmed the diagnosis of peripheral giant cell granuloma.